Anorectal Malformation (ARM), parent’s knowledge, Post PSARP care - Samiatin Samiatin; I Ketut Sudiana; Harmayetty Harmayetty (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Anal imperfect or without anal is congenital anomaly which more as known as anorectal malformation. Anorectal incident bas happen in 1 of 4000 to 5000 live birthing. Number of anal dilatation patients in the surgical clinic was about 10 patient’s average a day at Dr. Soetomo General Hospital. The studied aims to determine the relation between parent’s knowledge and anal dilatation Care post PSARP in Surgical Polyclinic Soetomo General Hospital.Methods: This study used a cross-sectional design. Population is taken from the patient's parents by post PSARP anal dilatation criteria’s. Total number of population sample were 21 people included. Samples were taken using consecutive non-random sampling. The independent variable was the knowledge of the parents. The dependent variable was the treatment anal dilatation Post PSARP. Knowledge of data collected by using questionnaires, whereas treatment with observation anal dilatation action on phantom. The data was analyzed by using Spearman's Rho Test with significance level α ≤ 0.05. Results: Spearman Rho test results showed a significant level p=0.045≤0.05 which means there are had a relation between parent’s knowledge with anal dilatation care post PSARP. The correlation coefficient r=0.442, this means there are had a variable correlation between parent’s knowledge with anal dilatation care post PSARP.Conclusion: The parent’s knowledge be affected by age, gender, education, jobs, experience and the information. It is suggested for further research to use the same issue with different method, except consecutive non random sampling method and from the different sciences because there are no anal dilatation research in Indonesia.